Comparative Study of Controllers for an Isolated Full Bridge Boost Converter Topology in Fuel Cell Applications - S. Vijaya Madhavi; G. Tulasi Ram Das (Institute of Advanced Engineering and Science, 2018)
Now a day’s renewable energy sources became an interesting area of research of which fuel cells are emerged as an alternative source for producing electricity to meet the energy crisis. This led to a research on power conditioning systems through which fuel cell is interfaced to the utility. Of the different converter topologies Isolated full bridge boost converter (IFBC) topology is most suitable for fuel cell applications. In this paper a Predictive Switching Modulator (PSM) Control is proposed for the converter topology and its performance is compared with Linear Peak Current Mode control (LPCM), Non-Linear Carrier Control (NLC).